Adrenal Hemangioma: A Common Tumor at Uncommon Site - Asnani, Ritu; Hosapatna Laxminarayana, Kishan Prasad; Kaliyat, Sajitha; Bhagvan, Kalale R.; Bhat, Praveen Kumar R.; Goel, Shreya (Journal of Health and Allied Sciences NU, 2021)
Adrenal hemangiomas are rare vascular tumors. These are benign, mostly nonfunctioning and asymptomatic. Cavernous adrenal hemangiomas are more common in the elderly, with female preponderance. A computed tomography (CT) scan can diagnose their benign nature. Most cases are managed surgically, and laparoscopy is the most common approach followed nowadays.A young female presented with nausea, pain, and a vague mass palpable in the right abdomen. With CT findings favoring benign lesion or nonfunctioning adenoma but symptomatic, the patient had to undergo diagnostic laparoscopy and adrenalectomy. Adrenal hemangiomas are rare lesions. Moreover, involving a young female further makes their diagnosis difficult. Hence, they must be kept as one of the differential diagnosis in evaluation of adrenal mass in young females.
Keywords: cavernous hemangiomas; benign tumors; dilated vascular channels